2018
DOI: 10.1007/s00216-018-1481-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of DEET and neonicotinoid pesticide biomarkers in human urine by online solid-phase extraction high-performance liquid chromatography-tandem mass spectrometry

Abstract: Neonicotinoid insecticides are widely used replacements for organophosphate and carbamate insecticides, but the extent of human exposure is largely unknown. On the other hand, based on urinary concentrations of DEET metabolites, human exposure to N,N-diethyl-m-toluamide (DEET) appears to be widespread. We developed a fast online solid-phase extraction high-performance liquid chromatography-isotope dilution tandem mass spectrometry (HPLC-MS/MS) method to measure in 200 μL of human urine the concentrations of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Interestingly, we already detected DME-ACE in the pre-dose urine sample at low levels, suggesting background exposures to ACE in the general population. This finding is in line with previous studies where DME-ACE has been analyzed in urine samples of the general population (Song et al 2021;Baker et al 2019) or after accidental intake of NNI-containing insecticide formulations (Taira et al 2013).…”
Section: Acetamipridsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, we already detected DME-ACE in the pre-dose urine sample at low levels, suggesting background exposures to ACE in the general population. This finding is in line with previous studies where DME-ACE has been analyzed in urine samples of the general population (Song et al 2021;Baker et al 2019) or after accidental intake of NNI-containing insecticide formulations (Taira et al 2013).…”
Section: Acetamipridsupporting
confidence: 92%
“…So far, with the exception of 5-OH-IMI and DME-ACE (Ospina et al 2019 ; Baker et al 2019 ; Wrobel et al 2020 ; Song et al 2021 ), the majority of published methods proposed the use of unchanged NNIs in urine as biomarkers of exposure (Osaka et al 2016 ; Ichikawa et al 2019 ; Harada et al 2016 ). For the first time, the present study identified promising and, most importantly, specific metabolites of NNIs in humans by a targeted approach, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CLO is registered in Benin, Côte d'Ivoire, Kenya, South Africa, Namibia, Zambia, and Zimbabwe; TCP formulations are registered in Nigeria, South Africa, Madagascar, Malawi, Zambia, and Zimbabwe; and DIN is legal in Kenya (Network of African Science Academies 2019). However, the massive use of THXM in cash crop and fruit farming systems in Ghana might also account for the high CLO exposure frequency (40%) recorded among the subjects, largely because CLO is a known metabolic product of THXM in mammalian species (Baker et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A method to do so was recently created and applied to the study of the urinary excretion of Roundup MON 52,276 co-formulants in exposed rats [ 146 ]. In the US, the CDC’s National Health and Nutrition Examination Survey [ 122 ] has recently developed new methods to test the most heavily applied herbicide (glyphosate [ 147 ]) and the insecticides people are most frequently exposed to via diet (the neonicotinoids [ 148 ]).…”
Section: Four Solutions To Curtail the Adverse Health Effects Of Pesticidesmentioning
confidence: 99%